Emotional Intelligence, Mental Distress and Handling Bullying in School Teachers - Ilyas, Sana; Nazir, Arooj; Baseer, Amber; Yasin, Wardah; Jahangir, Wajeeha (Pakistan Journal of Humanities and Social Sciences, 2024)
In process to combat bullying, it may be integral for well-being of students to have a teacher who they perceive as active, emotionally intelligent, resilient, and using an effective strategy of intervening to reduce bullying. The major goal of this study is to explore nexus between Mental Distress and Handling Bullying of School Teachers and Emotional Intelligence. A cross sectional Correlational research design was used and non-probability sampling technique was used to recruit the participants. The participants included private and government school teachers, N=292 (114 males and 164 females) with the age range of 25-50. The assessment tools (Urdu translated versions) used for this research were Handling Bullying Questionnaire (Bauman, Rigby, & Hoppa, 2008), Depression Anxiety and Stress Scale (DASS-21; Lovibond & Lovibond, 1995) and Emotional Intelligence scale (Batool & Khalid, 2011). A significant mean difference between private and government schools on handling bullying and emotional intelligence was evident by the results. Moreover, a significant difference was found between teacher’s emotional intelligence and number of years of experience. The results also indicated that there was a negative correlation between emotional intelligence and mental distress. Positive correlations were also found between subscales of handling bullying and emotional intelligence. It was revealed that emotional intelligence was a significant negative predictor of mental distress. This study likely to give insight to the policy makers of Anti-bullying programs to focus on emotional intelligence of teachers to help them deal with bullying in students. Moreover, strategies can be planned to deal with mental distress of teachers so that they can perform their role well.